The current status of the use of genetic modification and editing to improve biodiversity and ecological sustainability - Gideon Sadikiel Mmbando; Kelvin Ngongolo (All Life)
Technologies like genetic modification and editing (GME) present exciting opportunities to improve ecological sustainability and biodiversity. They do, however, have several ethical quandaries. The advantages and challenges of using GME in the context of ecosystem restoration and strategies for mitigating climate change remained poorly unknown. This review highlights the current use of GME technologies in biodiversity, ecological integrity, and wildlife conservation for protecting a species’ genetic integrity and promoting environmental adaptation. We found that the slow use of GME technologies was due to the public's varied ethical perspectives, which are influenced by cultural, religious, and ethical consumerism factors. This study emphasizes the critical need for open and honest regulations, stakeholder involvement, and moral standards to successfully negotiate the morally complex dilemmas of genetic modification and editing technologies for biodiversity conservation and a sustainable future.